Hubungan Durasi dan Postur Duduk Terhadap Keluhan Low Back Pain pada Mahasiswa Kedokteran - Koswara, Jocelyn; Machrina, Yetty; Lubis, Mahrani; Amelia, Rina (Talenta Publisher, 2024)
Background: Low Back Pain (LBP) is the most common musculoskeletal disorder in the community with a global prevalence of 15-45% each year. Medical students are prone to LBP due to several risk factors such as long sitting duration and improper sitting posture during lectures. Objectives: This research is performed to determine the correlation between the duration and sitting posture during lectures on the incidence of LBP in medical students at Universitas Sumatera Utara (USU). Methods: This study used an analytical descriptive research design with a cross-sectional approach conducted in April 2023 at the Faculty of Medicine, Universitas Sumatera Utara. The sampling technique used is simple random sampling with 147 medical students selected as the research sample. Data was obtained from filling out PAD and BAPHY questionnaires. A Chi-square test was used to explore the association between the two variables and LBP while the logistic regression test was used to identify the dominating causes generating LBP. Result: The study's findings revealed that 40.1% of students reported having LBP problems, 72.1% reported sitting for more than seven hours, and 33.3% reported having a bad sitting posture. Chi-square analysis revealed a significant correlation between sitting duration and posture on complaints of LBP (RR = 1.69, p = 0.041 and RR = 1.69, p = 0.009). At a risk of 2,438 times, sitting position is the main factor contributing to LBP among medical students at USU. Conclusion: This research showed a correlation between duration and sitting posture on the incidence of LBP. Keyword: Low Back Pain, Medical Students, Seven Hours, Sitting duration, Sitting posture Latar Belakang: Low Back Pain (LBP) merupakan gangguan muskuloskeletal yang paling sering terjadi pada masyarakat dengan prevalensi global 15-45% setiap tahunnya. Mahasiswa kedokteran rentan mengalami keluhan LBP dikarenakan beberapa faktor risiko seperti durasi duduk yang lama dan postur duduk yang tidak ergonomis saat perkuliahan. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara durasi dan postur duduk saat perkuliahan terhadap keluhan LBP pada mahasiswa Fakultas Kedokteran Universitas Sumatera Utara. Metode: Penelitian ini menggunakan desain penelitian deskriptif analitik dengan pendekatan cross-sectional yang dilakukan pada bulan April 2023 di FK USU Medan. Populasi penelitian adalah mahasiswa FK USU angkatan 2021 yang dipilih dengan metode simple random sampling dengan jumlah sampel sebanyak 147 orang. Data diperoleh dari pengisian kuesioner PAD dan BAPHY. Untuk mengetahui hubungan kedua variabel dengan keluhan LBP dilakukan uji Chi-square dan uji regresi logistik untuk melihat faktor dominan penyebab keluhan LBP. Hasil: Dari hasil penelitian ditemukan terdapat 40,1 % mahasiswa yang mengalami keluhan LBP dengan durasi duduk > 7 jam sebesar 72,1% dan postur duduk yang tidak baik sebesar 33,3%. Analisis Chi-square menunjukkan terdapat hubungan bermakna antara durasi dan postur duduk terhadap keluhan LBP (RR = 1,69, p=0,041 dan RR = 1,69, p=0,009). Faktor dominan penyebab keluhan LBP pada mahasiswa FK USU angkatan 2021 adalah postur duduk dengan besar risiko sebesar 2,438 kali. Kesimpulan: Durasi dan postur duduk memiliki hubungan dengan keluhan LBP. Kata Kunci: Durasi duduk, Low Back Pain, Mahasiswa Kedokteran, Postur Duduk, Tujuh Jam